Asuhan Kebidanan Pada Ibu Hamil Trimester I Di PMB Nurwati Wilayah Kerja Puskesmas Air Tiris - Ramadhany, Yanita; Dhilon, Dhini Anggraini (Evidence Midwifery Journal, 2023)
The first trimester of pregnancy is the first trimester of pregnancy, during this period the growth of the fetus is in the range of 0-12 weeks where natural processes undergo physiological changes. The purpose of this study was to determine midwifery care for pregnant women in the first trimester at PMB Nurwati in the working area of ??the Air Tiris Public Health Center in 2022. This study used a descriptive observational research design with a case study approach, the research subjects in this study were first trimester pregnant women. Data was collected by conducting direct interviews with pregnant women, the respondent's family and physical examination. From the first visit to the second visit, management was carried out according to the problems complained of. The upbringing of Mrs. A, namely pregnant women with nausea, vomiting, dizziness and back pain. The results of the mother's examination were within normal limits, BP: 90/60 mmHg, N: 83x/minute, R: 20x/mrnit, S: 36.6 0C, BW: 54 Kg , pink conjunctiva, G3P2A0H2 11 weeks gestation, general condition good, no danger signs found. The results of this case study are expected to add references that can be used for further research.